2020
DOI: 10.1039/d0ra07739a
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective synthesis and application of isopulegol-based bi- and trifunctional chiral compounds

Abstract: A new family of isopulegol-based bi- and trifunctional chiral ligands such as triols, tetrols, aminodiols and aminotriols was developed from commercially available (−)-isopulegol with antibacterial, antifungal and antioxidant activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 95 publications
(91 reference statements)
0
31
0
Order By: Relevance
“…Our previous work demonstrated that the O -benzyloxy group on the cyclohexyl ring is much more effective to induce antimicrobial activity. Therefore, to explore the role of the configuration of the O -benzyloxy group, some (−)-isopulegol-based O -benzyl derivatives were also prepared under optimized condition and using literature information [ 68 ] ( Scheme 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous work demonstrated that the O -benzyloxy group on the cyclohexyl ring is much more effective to induce antimicrobial activity. Therefore, to explore the role of the configuration of the O -benzyloxy group, some (−)-isopulegol-based O -benzyl derivatives were also prepared under optimized condition and using literature information [ 68 ] ( Scheme 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Debenzylation of 4b provided 44 in a moderate yield whereas exposure of 44 to NaOH furnished 45 with the retention of stereochemistry [ 86 ]. The absolute configuration of O -benzyl derivatives 19a and 25a was determined by debenzylation together with reduction via hydrogenolysis over Pd/C [ 87 , 88 ] to provide triol 45 with stereochemical retention [ 68 ]. The stereochemical structure of epoxide 44 is well-known in the literature [ 72 ]; therefore, the absolute configuration of O -benzyl derivatives could also be determined ( Scheme 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations